2021
DOI: 10.47933/ijeir.972796
|View full text |Cite
|
Sign up to set email alerts
|

Siamese Sinir Ağı One-Shot Öğrenmeyi Kullanarak İmza Doğrulama

Abstract: With the acceleration of digitalization in all areas of our lives, the need for biometric verification methods is increasing. The fact that biometric data is unique and biometric verification is stronger against phishing attacks compared to password-based authentication methods, has increased its preference rate. Signature verification, which is one of the biometric verification types, plays an important role in many areas such as banking systems, administrative and judicial applications. There are 2 types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…Arisoy [6] proposed a writer-independent signature verification system based on one-shot learning. Siamese neural network was performed in order to recognize authentic signatures from fake ones.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Arisoy [6] proposed a writer-independent signature verification system based on one-shot learning. Siamese neural network was performed in order to recognize authentic signatures from fake ones.…”
Section: Related Workmentioning
confidence: 99%
“…Biological features include the face, fingerprint, palm, iris, and retina, while behavioral features include signature and voice. In many areas of our lives, such as banks, educational institutions, attendance monitoring systems, and official document verification, where the need for authenticity is paramount, handwritten signature verification has become an integral aspect [6]. Based on the technique of acquisition, signatures are divided into offline and online signatures.…”
Section: Introductionmentioning
confidence: 99%
“…Zhou et al [41] aimed to enhance the features extraction phase in offline signature verification by extracting two types of features (static and dynamic), through combine gray level co-occurrence matrix (GLCM) with HOG, and classify the output with support vector machine (SVM) and dynamic time warping (DTW), the study indicated that improving the features extraction phase has positively affected the classification process. Additionally, Arisoy [42] used deep learning algorithms CNN and Siamese Network to improve signature verification, the proposed method was implement on four datasets (4NSigComp2012, SigComp2011, 4NSigComp2010, and BHsig260), and achieved accuracy of 93.23, 90.11, 89.99, and 92.35 respectively. In addition, Tahir and Ausat [43] used Artificial Neural Network to improve offline signature verification system, the proposed method used many features include Baseline Slant Angle (BSA), Aspect Ratio (AR), and Normalized Area (NA), and achieved accuracy of 82.5.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…In verification, a test signature is compared with a model signature to check whether the test signature is genuine or counterfeit. The intrapersonal and interpersonal variabilities in signing induce changes depending on factors such as the space available for signing, the type of pen used, and the psychophysical condition of the signer, a key challenge in both signature identification and verification [2]. Signatures can now be identified in two ways: offline and online.…”
Section: Introductionmentioning
confidence: 99%